De temporum ratione : Quadrivium und Gotteserkenntnis am Beispiel Abbos von Fleury und Hermanns von Reichenau - Germann, Nadja (Studien und Texte zur Geistesgeschichte des Mittelalters ;, 2006)
This study examines the scientific interests and rationality which find expression in the quadrivial sources of the 9th to 11th centuries, arguing on this basis for the existence of a 'discovery of nature' already prior to the 12th century. It focuses on the theme of 'time', exemplified by Abbo of Fleury's Computus, as well as Hermann of Reichenau's Epistola de quantitate mensis lunaris, Abbreviatio compoti and Prognostica. The systematic and historical background of the study is established through analysis of Alcuin's De vera philosophia, Bede's De temporum ratione and the computistic-astronomical anthologies which were the predominant genre during this period. The volume is complemented by fourteen illustrations and an appendix including Hermann's heretofore unedited texts, the Abbreviatio compoti and Prognostica.